Effects of salinity on seedling gemination and growth of early seedlings of the \(Najas indica\) (Willd.) Cham - Dang, Xuan Thi Le; Phan Thi, Thuy Hang; Ton, That Phap; Hoang, Cong Tin; Luong, Quang Doc (Vietnam Journal of Marine Science and Technology, 2022)
Najas indica (Willd.) Cham. is a freshwater submerged aquatic vegetation. N. indica is an annual plant. Therefore, seeds in the sediment and the survival and growth of seedlings play an important role in re-establishing new populations of the species. The purpose of this study was to determine the seed density in the sediment, examine the effect of salinity on seedling germination from seeds, and assess the impact of the salinity on the growth of early seedlings of N. indica under the experimental condition. The seed density of N. indica was highest from September to November and the lowest in May to July 2018. Seedlings of the species were observed in the range of salinity from 0–15‰. No seedling was recorded at 20‰ salinity during the experimental period. The number of seedlings, growth rate, shoot length, and the number of internodes of seedlings of N. indica, all had maximum values at a salinity of 5‰, while leaf length tended to decrease with increasing salinity. The study showed that the optimum salinity for seedling germination from seeds and growth of seedlings of N. indica species from the Cau Hai lagoon was at 5‰ salinity. The study results supply the necessary information for the protection and development of meadows of the N. indica species in the lagoon environment of Vietnam.